2012
DOI: 10.5194/acp-12-5259-2012
|View full text |Cite
|
Sign up to set email alerts
|

Signals of El Niño Modoki in the tropical tropopause layer and stratosphere

Abstract: Abstract. The effects of El Niño Modoki events on the tropical tropopause layer (TTL) and on the stratosphere were investigated using European Center for Medium Range Weather Forecasting (ECMWF) reanalysis data, oceanic El Niño indices, and general climate model outputs. El Niño Modoki events tend to depress convective activities in the western and eastern Pacific but enhance convective activities in the central and northern Pacific. Consequently, during El Niño Modoki events, negative water vapor anomalies oc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
67
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 137 publications
(69 citation statements)
references
References 59 publications
2
67
0
Order By: Relevance
“…It suggested that during EN, EP-ENSO events influence the North Pacific low in the winter and subsequently increase the planetary wave forcing and reduce the strength of the polar vortex. However, there are also controversies relating to the response of the NH to both types of ENSO, CP ENSO (Graf and Zanchettin 2012;Xie et al 2012;Hegyi and Deng 2011) and EP ENSO (Mitchell et al 2011;Manzini et al 2006) as models differ with observation. It is noteworthy that though CP ENSO and ENSO Modoki are the same in main features, they still differ in details; the same is also true for EP and Canonical ENSO.…”
Section: Further Examinedmentioning
confidence: 99%
See 1 more Smart Citation
“…It suggested that during EN, EP-ENSO events influence the North Pacific low in the winter and subsequently increase the planetary wave forcing and reduce the strength of the polar vortex. However, there are also controversies relating to the response of the NH to both types of ENSO, CP ENSO (Graf and Zanchettin 2012;Xie et al 2012;Hegyi and Deng 2011) and EP ENSO (Mitchell et al 2011;Manzini et al 2006) as models differ with observation. It is noteworthy that though CP ENSO and ENSO Modoki are the same in main features, they still differ in details; the same is also true for EP and Canonical ENSO.…”
Section: Further Examinedmentioning
confidence: 99%
“…The connection of ENSO with NH polar region through polar vortex or wave propagation is not captured well by models around Greenland area. Various studies discussed the controversies Blank in any cell means not observed or discussed in that category, while 'x' means no models match that criteria relating to connection between ENSO and NH polar region in both phases of ENSO, e.g., Modoki ENSO (Xie et al 2012;Graf and Zanchettin 2012;Hegyi and Deng 2011) and Canonical ENSO (Mitchell et al 2011;Manzini et al 2006). Identified good models are low top (EN)-inmcm4, FIO-ESM; low top (LN)-GFDL-ENM2G, ACCESS1-3, bcccsm1-1; high top (EN)-GFDL-CM3, HadGEM2-CC, MIROC-ESM; high top (LN)-no model.…”
Section: Sst-imentioning
confidence: 99%
“…Enhanced planetary wave driving, higher polar lower stratospheric temperatures, and a weaker Antarctic jet have also been identified in response to a different definition of WPEN events. Specifically, Zubiaurre and Calvo [2012] and Xie et al [2012] used the El Niño Modoki index [Ashok et al, 2007], a different metric by which to identify WPEN events, and found SH responses consistent with Hurwitz et al [2011aHurwitz et al [ , 2011b.…”
Section: Introductionmentioning
confidence: 99%
“…Variations in tropical sea surface temperature (SST) associated with ENSO, are an important factor in the modulation of the planetary wave activity in the Northern Hemisphere that affects the interannual variability of temperature and ozone levels in the northern polar stratosphere (Sassi et al, 2004;Manzini et al, 2006;Calvo et al, 2004Calvo et al, , 2009Cagnazzo et al, 2009;Hu and Pan, 2009;Hurwitz et al, 2011a, b;Zubiaurre and Calvo, 2012;Xie et al, 2012). The long-term trend in tropical SST also has a correspondence to the trend of temperature in the southern polar stratosphere (Grassi et al, 2005(Grassi et al, , 2006Hu and Fu, 2009;Li et al, 2010;Clem et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that the SST changes in the eastern Pacific, the Indo-Pacific warm pool, and the Atlantic can significantly influence the northern polar stratosphere (Calvo et al, 2004Hoerling et al, 2001Hoerling et al, , 2004Cagnazzo et al, 2009;Hu and Fu, 2009;Hu and Pan, 2009;Li et al, 2010;Hurwitz et al, 2011a, b;Lin et al, 2012;Zubiaurre and Calvo, 2012;Xie et al, 2012;Li and Chen, 2014). SST variations in some regions can excite Rossby wave trains, and those waves can propagate into the northern middle-and high-latitude stratosphere (Gettelman et al, 2001;Sassi et al, 2004;Manzini et al, 2006;García-Herrera et al, 2006;Taguchi and Hartmann, 2006;Hartmann, 2007, 2008;Free and Seidel, 2009).…”
mentioning
confidence: 99%